Significance of myocardial injury on in-hospital clinical outcomes of in-hospital and COVID-19 patients - Pooja Vyas; Ashish Mishra; Kunal Parwani; Iva Patel; Dhara Dhokia; Trishul Amin; Prarthi Shah; Tanmay Boob; Rujuta Parikh; Radhakishan Dake; Khamir Banker (Journal of Cardiovascular and Thoracic Research, 2023)
Introduction: Acute Myocardial injury defined by increased troponin I level is associated with poor in-hospital outcomes and cardiovascular complications in patients with COVID-19. The current study was designed to determine the implications and clinical outcome of myocardial injury in COVID-19. Methods: This retrospective study included hospitalized COVID-19 patients. Myocardial injury was defined by high sensitivity Troponin I (hs-TNI)≥26ng/l. Cardiac biomarkers, inflammatory markers and clinical data were systemically collected and analyzed. Hazard ratio for in-hospital mortality and logistic regression for predictors of acute myocardial injury were analyzed. Results: Of the 1821 total patients with COVID-19, 293(16.09%) patients died and 1528 (83.91%) patients survived. Patients who died had significantly higher association with presence of cardiovascular risk factors, severe CTSS ( CT severity score ) and myocardial injury as compared to survived group. 628 (34.5%) patients had evidence of myocardial injury and they had statistically significant association with cardiovascular risk factors, in-hospital mortality, procalcitonin; higher hospital, and ICCU stay. We found significant hazard ratio of diabetes (HR=2.66, (CI:1.65-4.29)), Severe CT score (HR=2.81, (CI:1.74-4.52)), hs-TNI≥26 ng/l (HR=4.68, (CI:3.81-5.76)) for mortality. Severe CTSS score (OR=1.95, CI: 1.18-3.23, P=0.01) and prior CVD history (OR=1.65, CI:1.00-2.73, P=0.05) were found significant predictors of myocardial injury in regression analysis. Conclusion: Almost one third of hospitalized patients had evidence of acute myocardial injury during hospitalization. Acute myocardial injury is associated with higher hospital and ICCU stay, mortality, higher in-hospital infection which indicates more severe disease and the poor in-hospital outcomes.